PERTANGGUNGJAWABAN HUKUM KANTOR PERTANAHAN ATAS TUMPANG TINDIH SERTIPIKAT HAK ATAS TANAH DALAM PENDAFTARAN TANAH SISTEMATIS LENGKAP - Yuskar Rakhmatika; Putra Hutomo; Felicitas Sri Marniati (Journal of Innovation Research and Knowledge, 2025)
Article 2 paragraph (2) ATR/BPN Ministerial Regulation No. 6 of 2018 states that PTSL aims to increase legal certainty and protection for land, make it easier for people to process land certificates, and prevent land disputes. However, in practice, land title certificates overlap, where land that already has legal proof of ownership is instead registered in the name of another party. The problem formulation in this research is: What are the legal consequences of overlapping land title certificates in complete systematic land registration? and what is the legal responsibility of the land office for overlapping land title certificates in complete systematic land registration? Theory of Legal Consequences according to R. Soeroso and theory of legal responsibility according to Hans Kelsen.The method used in this research is normative juridical research, which relies on library materials or secondary data derived from primary, secondary, and tertiary legal sources. The research approach employed includes statutory, conceptual, analytical, and case-based approaches. Legal materials are collected by identifying and compiling positive legal regulations, literature from books, journals, and other legal sources. The analysis of legal materials is conducted through systematic, grammatical, and analogical legal interpretation.The research results show that the legal consequence of overlapping land title certificates in complete systematic land registration is that the certificates become administratively defective. This happens because there is more than one legal status for one piece of land. Even though a land certificate is strong evidence, the certificate is not absolute and can be canceled if there is evidence showing that the issuance of the certificate did not comply with procedures or there was an error in the transfer of rights. Thus, parties who are disadvantaged by the issuance of overlapping certificates in the complete systematic land registration can request the cancellation of the issuance of administratively defective certificates through the State Administrative Court. The legal responsibility of the Land Office for overlapping land title certificates in a complete systematic land registration is that the Land Office is absolutely responsible for overlapping land title certificates in a complete systematic land registration. In this case, the Land Office is obliged to resolve disputes that arise due to errors in issuing overlapping certificates, in accordance with court decisions. The Land Office is also required to revoke and delete certificates with administrative defects from the land book and pay court costs arising from the dispute.